2022
DOI: 10.1101/2022.09.23.509067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of Mmu17 non-Hsa21 orthologous genes in the Ts65Dn mouse model of Down syndrome: the “gold standard” revisited

Abstract: Despite many successful preclinical treatment studies to improve neurocognition in the Ts65Dn mouse model of Down syndrome (DS), translation to humans has failed. This raises critical questions about the appropriateness of the Ts65Dn mouse as the gold standard for DS research given that it carries, in addition to Mmu16 orthologous genes, triplication of 50 Mmu17 non-orthologous genes that might contribute to the observed brain and behavioral phenotypes. We used the novel Ts66Yah mouse that carries both an extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…To circumvent this major limitation, CRISPR/Cas9-based genome editing approach has recently been used to remove the 46 genes from the Mmu17 centromeric region of the marker chromosome [ 159 ]. Behavioral and neurocognitive characterization of the refined Ts66Yah mice (trisomic for only Mmu16 genes) showed the conservation of key DS features, but with an overall milder phenotype compared to Ts65Dn mice [159] , [160] . It should be noted that a modified Ts65Dn strain, 5252, which shows attenuated severity of phenotypes compared to its original version and to the original Ts65Dn strain, was used to create Ts66Yah.…”
Section: Discussionmentioning
confidence: 98%
“…To circumvent this major limitation, CRISPR/Cas9-based genome editing approach has recently been used to remove the 46 genes from the Mmu17 centromeric region of the marker chromosome [ 159 ]. Behavioral and neurocognitive characterization of the refined Ts66Yah mice (trisomic for only Mmu16 genes) showed the conservation of key DS features, but with an overall milder phenotype compared to Ts65Dn mice [159] , [160] . It should be noted that a modified Ts65Dn strain, 5252, which shows attenuated severity of phenotypes compared to its original version and to the original Ts65Dn strain, was used to create Ts66Yah.…”
Section: Discussionmentioning
confidence: 98%
“…However, Ts65Dn contains about 55% of the orthologous protein‐coding genes found on Hsa21. It also carries additional trisomic genes from Mmu17 not found in Hsa21, complicating the genotype‐to‐phenotype outcomes in Ts65Dn mice (Guedj et al., 2023). The recent non‐mosaic transchromosomic TcMAC21 model has 93% of Hsa21 protein‐coding genes, making it the most genetically representative mouse model of DS (Kazuki et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Guedj et al. (2023) found an overexpression of Mmu17 non‐HSA21 genes in (embryonic) forebrain development of Ts65Dn mice. Studies performed on a variety of animal models have revealed significant links between the face and forebrain that regulate normal morphogenesis of these structures (Hu & Marcucio, 2009, 2021; Marcucio et al., 2005, 2011; Naqvi et al., 2021; Parsons et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, future experiments could be performed on the refined Ts65Dn model recently developed, the Ts66Yah, which retains the major features of DS, but showed an overall milder phenotype than Ts65Dn mice (Duchon et al, 2022). However, it is worth noting that the partial Ts65Dn model does not overexpress the Hsa21 orthologous genes carried by Mmu10 and Mmu17, which raises questions about the relevance of this partial mouse model as a standard for DS research (Guedj et al, 2022). Therefore, it is important to conduct comparative studies in different mouse models for DS, each with its limitations in recapitulating the full spectrum of human DS.…”
Section: Discussionmentioning
confidence: 99%